Modeling Teacher Supports Toward Self-Directed Language Learning Beyond the Classroom: Technology Acceptance and Technological Self-Efficacy as Mediators - Pan, Xiaoquan; Chen, Wei (Frontiers in Psychology, 2021)
This study explored the contributions of teacher supports toward students’ self-directed language learning beyond the classroom and investigated whether technology acceptance and technological self-efficacy could be the mediators between teacher supports and students’ self-directed language learning in a sample of Chinese undergraduate students. A total of 197 freshmen students in one university in Eastern China participated in the questionnaires concerning teacher supports, technology acceptance, technological self-efficacy and self-directed language learning. The study highlighted the results: (1) perceived usefulness mediated the relationship between teacher affective supports and students’ self-directed language learning as well as the relationship between teacher capacity supports and students’ self-directed language learning; (2) technological self-efficacy mediated the relationship between teacher affective supports and students’ self-directed language learning as well as the relationship between teacher behavior supports and students’ self-directed language learning; and (3) perceived easy of use had no noticeable mediating functions, but exerted an indirect influence on students’ self-directed language learning. These findings extended previous researches by considering both the external factors (i.e., teacher supports) and the internal factors (i.e., technology acceptance and technological self-efficacy) of influencing students’ self-directed language learning, thereby contributing to enhancing our understanding of the joint drive of the inherent and extrinsic power mechanisms. This study indicated the significance of elevating teachers’ awareness of the substantial supports in enhancing students’ self-directed language learning beyond the classroom and would inform that the future research on teachers’ compliance in relation to technology use be converted from institutional mandates into teachers’ conscientious behaviors.